(untitled) (Vietnam Journal of Community Medicine, 2026)
Objective: Evaluate the results of endovascular stent grafting for the treatment of chronic aortic-iliac artery stenosis at the University Medical Center of Ho Chi Minh City. Subjects and methods: Retrospective descriptive case series on 36 patients treated with stent grafting for chronic aortic-iliac artery stenosis. Demographic data, clinical characteristics, and imaging features of the lesions were collected. Follow-up included clinical assessment, Doppler ultrasound, and ankle-brachial index. Endovascular intervention using a stent graft was performed to reconstruct the stenotic lesion at the aortic-iliac artery bifurcation. The rate of recanalization and re-intervention of the target lesion during follow-up was evaluated. Results: Of the 36 patients, 77.8% were diagnosed with intermittent claudication and 22.2% with severe limb ischemia. The majority (83.3%) were TASC II D lesions, with the remainder being B and C lesions (8.3% each). The median follow-up time was 12 months. The technical success rate was 91.7%. The ankle-brachial index improved significantly from 0.55 ± 0.24 preoperatively to 0.84 ± 0.17 postoperatively. The rate of minor complications within 30 days was 16.6%, and there were no major complications. The median hospital stay was 4 days. At 6 months and 1 year follow-up, 91.6% and 94.4% of patients, respectively, showed at least one Rutherford grade improvement clinically. The primary and secondary reperfusion rates were 86.1% and 88.9%, respectively, after 1 year. The rate of patients not requiring re-intervention on the target lesion due to clinical indications was 83.3% after 1 year of follow-up. Conclusion: Endovascular stenting of the aortic bifurcation is a safe and feasible technique for treating chronic aortic-iliac artery stenosis with good results after 1 year in terms of both reperfusion rate and clinical improvement.